Examining the Role of Masstige Value Between Celebrity Endorsement and Consumer Engagement of Fashion Brands: An Empirical Study - Aneela Jabbar; Adnan Ahmed Sheikh; Syed Hassan Raza (International Journal of Business and Economic Affairs, 2023)
Masstige marketing has attained significant consideration in recent times as a theoretically essential and practically applicable notion. Masstige’s strategy includes all those actions focused on positioning the products for the masses with a slight price decrease. Product promotional strategies determine its success. Even though it has been known as a significant strategic construct, the emerging concept requires additional examination for improved understanding. This research finds considerable gaps in the existing literature on fashion apparel masstige brands and aims to bridge them. The objective of the present study is to empirically examine the factors that generate masstige value and its outcome. The current study uncovers the role of celebrity endorsement in influencing the masstige value that further influences consumer brand engagement. Data were gathered from 415 respondents, and PLS-SEM was used to verify the proposed hypotheses. The results show that celebrity endorsement significantly influences the masstige value. In addition, the research work highlighted that masstige value influences consumer brand engagement. Mediation analysis highlighted the role of masstige value as a mediator in the relationship between celebrity endorsement and consumer brand engagement. The study’s results can help marketers to promote their masstige brands by adopting the celebrity endorsement strategy